IMPLEMENTASI METODE INQUIRY DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM UNTUK MENINGKATKAN PEMAHAMAN SEJARAH ISLAM DI MA MUHAMMADIYAH 2 PATEAN - Winda Maulida Rahmah; Achmad Kurniawan Pasmadi (As-Sulthan Journal of Education, 2025)
Islamic Cultural History Learning plays an important role in shaping students' understanding of the values, culture, and development of Islamic civilization from time to time. However, conventional learning approaches often cause boredom and difficulty in understanding the material in depth. This study aims to examine the implementation of the inquiry method in Islamic Cultural History learning and its impact on improving students' understanding of Islamic history. The inquiry method was chosen because it is participatory and investigative, which allows students to actively build knowledge through the process of asking questions, collecting information, analyzing data, and drawing conclusions. The results of the study indicate that the application of the inquiry method can significantly increase students' learning engagement and conceptual understanding of Islamic cultural history material. Thus, the inquiry method can be used as an alternative effective and relevant learning strategy in the context of more meaningful and contextual Islamic history education